God's Faithfulness in Hosea 3:1-5: The Journey that Brings Home - Maritaisi Hia; Harefa, Ya'aro (Sekolah Tinggi Teologi Trinity Parapat, 2023)
This article is an analysis of God's faithfulness in Hosea 3:1-5. God used the metaphor of the story of Hosea and Gomer to express His loyalty to the Israelites who always committed spiritual prostitution. He redeemed them from sin. This is described in the story of Hosea as the existence of God who wants to love again and buy his wife Gomer as the existence of the Israelites. Using four layer meaning exegesis method (historia, theoria, moral, and anagogic), this research shows that God's faithfulness to the Israelites can be seen through a process of bringing the Israelites back to God, in which there is the role of God and also humans. Men feel God's faithfulness when they repent and restored by Him.